Relationship Between Self-Efficacy and Quality of Life in Elderly With Type 2 Diabetes Mellitus in Community Health Centers - Agritubella, Syafrisar Meri; Fatmi, Yoza Misra (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2023)
Living with diabetes can be emotionally and mentally demanding. As a chronic condition that requires condition self-management, it can sometimes be stressful, challenging and frustrating. This causes decreased productivity in T2DM patients. The aim of this study is to describe the relationship between self-efficacy and the Quality of life of T2DM patients at the Community Health Center. This research is a descriptive correlation with a cross-sectional study approach. The sampling technique using the Slovin Formula resulted in 120 people suffering form T2DM. The results show that 44,2% of elderly people have low self-efficacy, 50,8% of elderly people have poor quality of life. There is a significant relationship between self-efficacy and quality of life for elderly people with DM (p=0,000). Conclusion: Low Self-Efficacy tends to have a poor quality of life in elderly people with Type 2 DM.